Species composition and quantitative distribution of seaweeds in the sublittoral zone and on the continental slope in the northwestern Japan Sea - V. N. Kulepanov; E. N. Drobyazin (Известия ТИНРО, 2018)
Species composition and quantitative distribution of seaweeds on the shelf and continental slope of Primorye in the northwestern Japan Sea (depth 20–750 m) are considered on the data of trawl surveys conducted in 2015–2016. In total, 26 seaweed species were found: 16 Rhodophyta, 7 Phaeophyta, 1 Chlorophyta, and 2 species of sea grass. Most of the species were found on the depth < 60 m where the biomass of seaweeds varied from 44 to 569 kg/km2. On the depth about 100 m, the biomass decreased signifcantly to the value < 36.4 kg/km2, and only single seaweeds were found on the depth > 700 m. There is supposed that the lowest limit of the phytal zone in the northwestern Japan Sea is located at the depth 50–100 m.